Inflammation in Heart Failure: Mechanisms and Therapeutic Strategies - Yu, Jiang; Zhou, Guoxiang; Guo, Yongzheng; Long, Yang (Cardiovascular innovations and applications, 2025)
Cardiovascular disease remains a leading cause of death and disability worldwide. Heart failure (HF) is the end stage of various cardiovascular diseases. Despite recent advancements in understanding of HF pathogenesis and treatment, the prognosis of patients with HF remains poor. Inflammation is a key player in the development of HF, and its role in the pathogenesis of HF has been extensively studied. Inflammation is associated with elevated HF risk and adverse prognosis. Targeting cardiac inflammation has been suggested as a promising treatment strategy for HF. However, almost all clinical trials on the anti-inflammatory treatment of HF have not indicated improved clinical outcomes, and some have reported deterioration of the condition, possibly because of limited understanding of the specific role of inflammation in HF. The summary of inflammatory mechanisms contributing to the pathogenesis of different HF types, current anti-inflammation therapies for HF, and the results of clinical trials could provide new perspectives for understanding and targeting the role of inflammation in HF through the development of effective clinical therapeutic strategies.